Utilization of Digital Learning Media in Arts and Culture Education in Indonesian Schools Abroad - Afiah, Nur; Dayu, Dian Permatasari Kusuma; Istiq'faroh, Nurul (Journal of Innovation and Research in Primary Education, 2025)
This study explores the utilization of digital learning media in arts and culture education within the context of Indonesian schools abroad (Sekolah Indonesia Luar Negeri/SILN). Through a systematic literature review, the research investigates how digital tools can support the preservation and promotion of Indonesian cultural identity while enhancing student engagement and creativity. The findings reveal that digital media, including interactive multimedia platforms and virtual learning environments, play a significant role in making arts and culture education more accessible, interactive, and relevant for students living in multicultural environments. Benefits include increased student motivation, collaborative learning opportunities, and the development of critical digital skills. However, the study also identifies several challenges, such as limited technological infrastructure, uneven access to digital resources, and insufficient teacher training in integrating technology into culturally rich curricula. The research highlights the need for a more comprehensive approach that includes professional development for educators, curriculum adaptation, and investment in digital infrastructure. While the study is limited by its reliance on secondary sources, it provides valuable insights into the potential and limitations of digital media in global cultural education. These findings contribute to the ongoing discourse on digital transformation in education and offer practical recommendations to enhance the implementation of digital learning in arts and culture, particularly in international school settings.